An NMR crystallography investigation of furosemide. (11th October 2018) - Zilka, Miri; Yates, Jonathan R.; Brown, Steven P.
Abstract: This paper presents an NMR crystallography study of three polymorphs of furosemide. Experimental magic‐angle spinning (MAS) solid‐state NMR spectra are reported for form I of furosemide, and these are assigned using density‐functional theory (DFT)‐based gauge‐including projector augmented wave (GIPAW) calculations. Focusing on the three known polymorphs, we examine the changes to the NMR parameters due to crystal packing effects. We use a recently developed formalism to visualise which regions are responsible for the chemical shielding of particular sites and hence understand the variation in NMR parameters between the three polymorphs. Abstract : There are 10 entries in the Cambridge Structural Database for crystal structures of furosemide, corresponding to three polymorphs. This is the starting point for an NMR crystallography study that combines DFT‐based geometry optimisation and GIPAW calculation of NMR parameters with experimental solid‐state MAS NMR. The analysis includes the calculation of nuclear independent chemical shifts (NICS) as well as the presentation of decomposition maps for visualising the effect of aromatic ring currents on NMR chemical shifts.